THE EFFECT OF PROFESSIONAL ALLOWANCE ON TEACHER PERFORMANCE WITH PROFESSIONALISM AS AN INTERVENING VARIABLE AT THE BINJAI CITY EDUCATION OFFICE - Joko Waskitono; Muhammad Isa Indrawan (Berajah Journal, 2023)
In the world of education, teachers have a very important role in developing human resources through education. The teaching profession has the task of educating, teaching and training. Educating means continuing and developing life values, teaching means continuing and developing knowledge, training means developing skills in students. This research was conducted to analyze the effect of professional allowance on the performance of schoolteachers with professionalism as an intervening variable. The research location was carried out in the Binjai City Education Office. The population in this study amounted to 70 teachers with a saturated sample. The model used in this research is path analysis and the measurement tool for this research is Smart PLS 3.3.3. The result of this study is that professionalism has a positive and significant effect on teacher performance. Professional allowance has a negative and insignificant effect on teacher performance. Professional Allowances have a positive and significant effect on Professionalism Professional Allowances have a positive and significant effect on teacher performance through professionalism.